Effects of thyroid hormones on muscle and bone in mice - Akihito Nishikawa; Naoyuki Kawao; Yuya Mizukami; Ryota Kishigami; Koji Goto; Hiroshi Kaji (Experimental and Clinical Endocrinology & Diabetes, 2026)
Abstract Background: The significance of muscle–bone interactions in bone metabolism and the pathophysiology of osteoporosis has been recognized. However, the effects of thyroid hormones on muscle–bone interactions remain unclear. Methods: We herein investigated the effects of hyperthyroidism on muscle and bone by administering L-thyroxin to male mice for 4 weeks. Results: A micro-computed tomography analysis showed that the administration of L-thyroxin significantly decreased trabecular bone mineral density, bone volume/tissue volume, trabecular number, trabecular thickness, and connectivity density at the femurs of mice and slightly reduced cortical thickness. However, the administration of L-thyroxin did not affect muscle mass in the lower limbs, tissue weights of the soleus and gastrocnemius muscles, or grip strength. Among the myokines examined, the administration of L-thyroxin significantly decreased the messenger RNA level of follistatin in the soleus muscle and simple regression analyses showed a positive correlation between follistatin levels and bone volume/tissue volume; however, it did not affect serum follistatin levels. Conclusions: The present results suggest that hyperthyroidism induced by the administration of L-thyroxin caused trabecular-dominant osteopenia without reducing muscle mass or grip strength in mice. The direct effects of thyroid hormones on bone, but not muscle–bone interactions, may be crucial for hyperthyroidism-induced osteoporosis.